Durability of high performance self-compacting concrete with granulometrically optimized slag cement. (6th September 2021) - Irico, Sara; Qvaeschning, Dirk; Mutke, Sabine; Deuse, Thomas; Gastaldi, Daniela; Canonico, Fulvio
Highlights: The addition of granulometrically optimized slag cement for robust and durable SCC. The durability is improved by blending 35 wt-% CEM III/C with CEM I. The chloride migration, freeze/thaw scaling and sulfate attack are mitigated. SCC with a low heat high belite cement shows high intrinsic durability behavior. Abstract: The addition of granulometrically optimized slag cement (CEM III/C) in a high-performance concrete mix is a promising technical solution in order to produce a robust, durable and sustainable SCC with tailored properties. The addition of 35 wt-% CEM III/C was implemented in three cements with different C3 S/C2 S and C3 A/C4 AF ratios (including a high-belite cement). The paper presents a comprehensive study covering the physical–mechanical performance and the chemical and mineralogical influence of the implementation of CEM III/C. The strengths were increased and the rheological properties improved. The chloride migration, the freeze/thaw sensitivity, and the sulfate attack expansion were reduced in favor of the sustainability.